2014
DOI: 10.1016/j.jbi.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Learning Bayesian networks for clinical time series analysis

Abstract: The model learning methods are capable of finding good predictive models for our COPD data. Model averaging over models based on bootstrap replications is able to find a good balance between true and false positive rates on predicting COPD exacerbation events. Temporal naive Bayes offers an alternative that trades some performance for a reduction in computation time and easier interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…It turns out that it is possible to predict at least part of the exacerbations a day in advance with the best model resulting in an AUC of 0.82. [20] The results from the pilot studies with respect to the usability goal revealed that the patients' impression of the system after using it is fairly positive. This early feedback from actual COPD patients is important for these kinds of systems because acceptance is often a concern.…”
Section: Home Monitoring Of Copd Patientsmentioning
confidence: 99%
“…It turns out that it is possible to predict at least part of the exacerbations a day in advance with the best model resulting in an AUC of 0.82. [20] The results from the pilot studies with respect to the usability goal revealed that the patients' impression of the system after using it is fairly positive. This early feedback from actual COPD patients is important for these kinds of systems because acceptance is often a concern.…”
Section: Home Monitoring Of Copd Patientsmentioning
confidence: 99%
“…Based on their content, the selected papers were tabled into predictive models used in CD identification (Table 1) and pathologies with model usage, along with their strengths and limitations ( Table 2). There is currently no complete AI system that can able to detect a couple of abnormalities overall through the human body [38].…”
Section: Quality Evaluationmentioning
confidence: 99%
“…Bayesian Networks models (or Bayesian Networks, shortly BNs) are a class of multivariate statistical models that allow for the representation of probabilistic relationships among a set of variables by means of a graph [37,50,47,34]. Bayesian Networks have been extensively applied in a variety of fields, from genomic and gene expression analysis [21,54,57] to official statistics [59,51], ecology [44,28], fault diagnosis [26], healthcare [36,62] and climate data applications [16,45,64].…”
Section: Bayesian Networkmentioning
confidence: 99%